MAKING WORKING CONTRACTS WITH DUTA ELEKTRONIK - Suryanto Suryanto; Eko Nurisman (Universitas Internasional Batam, 2022)
An employment contract is an agreement that is agreed between workers and employers in written and oral forms that exist regarding parts of the rights and obligations of both parties in accordance with applicable regulations. With the existence of a work contract agreement that is approved by both parties, it is already in a legal bond that must be carried out if it is not implemented then there are penalties for those who violate it for workers or employers. In the employment contract, there are many things that must be considered so that the parties must read more carefully in an agreement to get a profit or loss in the written employment contract. Employment contracts usually provide losses for parties who violate the employment contract which can get fair punishment for both parties. Written or oral employment contracts are made in the workplace or a room that can be explained or read in their entirety to understand the contents of the agreement determined by the company. Employment contracts are also used to avoid unwanted events by the company and to carry out cooperation with the company properly without any obstacles or unwanted events occurring. In the case of an employment contract, it is necessary to know the contents of the employment contract agreement that makes both parties feel balance or commensurate with the advantages and disadvantages signed by the worker.